2011
DOI: 10.1007/s11120-011-9635-3
|View full text |Cite
|
Sign up to set email alerts
|

The carbonic anhydrase isoforms of Chlamydomonas reinhardtii: intracellular location, expression, and physiological roles

Abstract: Aquatic photosynthetic organisms, such as the green alga Chlamydomonas reinhardtii, respond to low CO(2) conditions by inducing a CO(2) concentrating mechanism (CCM). Carbonic anhydrases (CAs) are important components of the CCM. CAs are zinc-containing metalloenzymes that catalyze the reversible interconversion of CO(2) and HCO(3)(-). In C. reinhardtii, there are at least 12 genes that encode CA isoforms, including three alpha, six beta, and three gamma or gamma-like CAs. The expression of the three alpha and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
187
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(194 citation statements)
references
References 110 publications
(174 reference statements)
6
187
1
Order By: Relevance
“…LCIB, located around the pyrenoid, traps CO 2 , either escaping from the pyrenoid or entering from outside the cell, into the stromal HCO 3 2 pool. This stromal HCO 3 2 pool then provides substrate to the pyrenoid thylakoid tubules for CAH3-catalyzed dehydration to CO 2 for Rubisco, as described in previous CCM models (Spalding et al, 1983b;Mitra et al, 2005;Spalding, 2008;Moroney et al, 2011).…”
Section: Co 2 Inhibition Of Lcia-mediated CI Uptakementioning
confidence: 97%
See 1 more Smart Citation
“…LCIB, located around the pyrenoid, traps CO 2 , either escaping from the pyrenoid or entering from outside the cell, into the stromal HCO 3 2 pool. This stromal HCO 3 2 pool then provides substrate to the pyrenoid thylakoid tubules for CAH3-catalyzed dehydration to CO 2 for Rubisco, as described in previous CCM models (Spalding et al, 1983b;Mitra et al, 2005;Spalding, 2008;Moroney et al, 2011).…”
Section: Co 2 Inhibition Of Lcia-mediated CI Uptakementioning
confidence: 97%
“…Genetic analysis of LCIB/CAH3 double mutants indicated that LCIB functions downstream of CAH3, a thylakoid lumen CA (Duanmu et al, 2009b). Because CAH3 catalyzes dehydration of accumulated HCO 3 2 to provide CO 2 for Rubisco inside the pyrenoid (Spalding et al, 1983b;Moroney et al, 2011), it has been hypothesized that LCIB captures CO 2 leaked from the pyrenoid, possibly by unidirectionally hydrating CO 2 back to HCO 3 2 (Duanmu et al, 2009b). If this hypothesis is correct, it also implies that LCIB may also function in active Ci accumulation by unidirectionally hydrating externally diffused CO 2 into the stromal HCO 3 2 pool (Wang and Spalding, 2014).…”
mentioning
confidence: 99%
“…Internal accumulation of C i occurs against a large concentration gradient, so accumulation must occur as HCO 3 2 because its permeability across lipid membranes is 1000-fold lower than that of CO 2 . However, Rubisco uses CO 2 as substrate, so, along with C i transporters, carbonic anhydrases (CAs), which catalyze interconversion of CO 2 and HCO 3 2 , also play important roles in the CCM, (Spalding et al, 1983a;Coleman and Grossman, 1984;Moroney et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…α-, β-, and γ-CA have been reported to be distributed widely in microalgae and higher plants, are zinc-metalloenzymes that catalyze the reversible interconversion of CO 2 and HCO 3¯ [29] . In higher plants, CAs play a vital role in the process of photosynthesis, respiration, ion absorption [30] .…”
Section: Discussionmentioning
confidence: 99%